2014
DOI: 10.1097/sla.0b013e31828b0fae
|View full text |Cite
|
Sign up to set email alerts
|

Rates, Patterns, and Determinants of Unplanned Readmission After Traumatic Injury

Abstract: Unplanned readmissions after discharge from acute care for traumatic injury are frequent, persist beyond 30 days, and are often related to potential complications of injury. Several patient-, injury-, and hospital-related factors are associated with the risk of readmission. Injury readmission rates should be monitored as part of trauma quality assurance efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 21 publications
12
80
3
Order By: Relevance
“…6 Finally, a recently published retrospective cohort study of 115,329 trauma patients in the Quebec trauma registry found a 5.9% unplanned 30-day readmission rate. 19 There was a significant rate of readmission within 12 months of 21.1%. They found that readmissions within 30 days in patients younger than 65 years old were as likely to be due to a new injury as to a complication from the original injury (30.8% and 31.6%); in patients 65 years or older, 33.2% were readmitted for complications of initial injury and 16.3% for a new injury.…”
Section: Commentmentioning
confidence: 97%
“…6 Finally, a recently published retrospective cohort study of 115,329 trauma patients in the Quebec trauma registry found a 5.9% unplanned 30-day readmission rate. 19 There was a significant rate of readmission within 12 months of 21.1%. They found that readmissions within 30 days in patients younger than 65 years old were as likely to be due to a new injury as to a complication from the original injury (30.8% and 31.6%); in patients 65 years or older, 33.2% were readmitted for complications of initial injury and 16.3% for a new injury.…”
Section: Commentmentioning
confidence: 97%
“…There is a relationship between comorbidities and readmissions after orthopaedic trauma surgery [23,35]. In orthopaedic surgery, comorbidities have been identified as predictors of mortality after arthroplasty, trauma surgery, and oncologic surgery [4,9,18,20,21,25,27,36].…”
Section: Introductionmentioning
confidence: 99%
“…This study used competing risk regression and shows that patients with the high risk of readmission in year after injury were those who had falls/severe head injury/ index ICU admission. Previous studies shown that 30-day readmission rates after trauma range from 4.2% to 13.3% 17,18,26 . Spector and colleagues 17 focused on older adults, finding a 30-day readmission rate which was higher than current study (13.3% vs 7.9%) 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, earlier studies have depicted that readmissions occur at hospitals other than the index establishment 26 . The detail of the CHARS database also allowed exclusion of elective readmissions, hence targeting unplanned rehospitalisation.…”
Section: Discussionmentioning
confidence: 99%